Experimental Investigation on the Characteristics of Hydrodynamic Stabilities in Francis Hydroturbine Models. (24th March 2014) - Su, Wen-Tao; Li, Xiao-Bin; Li, Feng-Chen; Wei, Xian-Zhu; Han, Wen-Fu; Liu, Shu-Hong
Abstract : This paper presents an experimental investigation of flow phenomena related to the characteristic frequencies of pressure fluctuation in Francis hydroturbine models. The experiments were carried out on two test rigs with two model runners having hydraulic similarities. Flow field around the guide vanes was measured with a particle image velocimetry (PIV) on the first PIV test rig. Flow structures at the inlet region of runner and in draft tube at different operating conditions were visualized on another hydrodynamic test rig. Analyses of dominant frequency of unsteady hydraulic behaviors in the tested hydroturbines were performed. It was observed that the main frequency of flow over the guide vanes and the dominant frequency of channel vortex equal the blade passing frequency; the dominant frequency of flow separation at the suction side of blade inlet equals the vane passing frequency; the vortex rope in the draft tube displays a low-frequency nature. The flow instabilities and fluctuations directly influence the running of hydroturbine, thus these experimental results could provide important evidence for the stability study of a real hydroturbine.